2017
DOI: 10.1097/inf.0000000000001471
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycoplasma pneumoniae Infection in Malagasy Children

Abstract: We report a prevalence of 18.2% for M. pneumoniae infection in children in Madagascar. The prevalence of M. pneumoniae infection was higher in the control patients than in asthmatic ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Bacterial and viral infections are the most common reasons that children receive medical care in clinics or small hospitals [ 1 , 2 ]. Because the symptoms exhibited by patients with bacterial and viral infections are similar, symptom-based examinations and history-taking are usually insufficient to distinguish between bacterial and viral infections, even by experienced doctors [ 3 ].…”
Section: Assessing Infectious Disease Among Children: the Need For Immentioning
confidence: 99%
“…Bacterial and viral infections are the most common reasons that children receive medical care in clinics or small hospitals [ 1 , 2 ]. Because the symptoms exhibited by patients with bacterial and viral infections are similar, symptom-based examinations and history-taking are usually insufficient to distinguish between bacterial and viral infections, even by experienced doctors [ 3 ].…”
Section: Assessing Infectious Disease Among Children: the Need For Immentioning
confidence: 99%
“…None of the clinical signs evaluated in this study showed statistically significant associations with M. pneumoniae . Other studies found no relationship between clinical presentation and CAP due to M. pneumoniae 42,54. These findings show that the diagnosis of CAP due to M. pneumoniae can rarely be established based on the clinical presentation alone.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, it is a significant cause leading to the hospitalization of children with community‐acquired pneumonia . The incidence of mycoplasma pneumonia in children is high, which accounts for 16%‐30% of community‐acquired pneumonia in children . It is generally mild, but it can be very serious, even involves extra pulmonary spread, such as central nervous system, mucosa and other organs, which seriously endangered the health of children .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…3,4 The incidence of mycoplasma pneumonia in children is high, which accounts for 16%-30% of communityacquired pneumonia in children. [5][6][7][8] It is generally mild, but it can be very serious, even involves extra pulmonary spread, such as central nervous system, mucosa and other organs, which seriously endangered the health of children. 4 Due to the serious side effects of tetracycline and fluoroquinolones on children, macrolides have become first choice for the treatment of mycoplasma pneumonia in children.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%